Māori Linked Administrative Data: Te Hao Nui - A novel Indigenous Data Infrastructure and Longitudinal Study - Boulton, Amohia; Theodore, Reremoana; Sporle, Andrew (The International Indigenous Policy Journal, 2023)
Worldwide, large amounts of administrative data are collected within official statistics systems on Indigenous Peoples. These data are primarily used for government and state policy purposes as opposed to by Indigenous Peoples to support Indigenous agendas (Taylor & Kukutai, 2017). In Aotearoa me Te Waipounamu New Zealand, Māori need high quality data to develop evidence-based policies and programs and to monitor government policies that impact on Māori. In this methodological paper, we describe uses of administrative data for Māori and current barriers to its use. We outline the development of a novel administrative data infrastructure and future longitudinal study. By explicating our Indigenous initiated, designed and controlled data project, we make a methodological contribution to Indigenous Data Sovereignty and Kaupapa Māori (Māori worldview) epidemiology.
Keywords: Indigenous data sovereignty; Māori; administrative data; policy; wellbeing; youth

Rethinking Claims-making as Māori Affairs Policy - Fleras, Augie; Maaka, Roger (He Pukenga Korero: a journal of Māori studies, 1998)
Keywords: crown policy; māori affairs; mātauranga māori; policy; social life and customs; treaty claims; tāngata whenua

Te Pītau o te Tuakiri: Affirming Māori Identities and Promoting Wellbeing in State Secondary Schools - Rata, Arama (2012)
Numerous researchers have posited links between ethnic identity and psychological wellbeing (Phinney, 1992; Martinez & Dukes, 1997; Roberts, Phinney, Masse, Chen, Robers, & Romero, 1999; Houkamau & Sibley, 2011), and Māori cultural interventions have been suggested as a means of promoting a range of positive outcomes (e.g. M. Durie, 1998; Durie, 2003b; Lawson-Te Aho, 1998). However, longitudinal evidence of causal pathways between Māori ethnic identity and psychological wellbeing remains scarce, and evidence of the positive impacts of cultural interventions is not well documented. The present thesis investigates Māori identity development in the context of State secondary schools, and explores the relationships between Māori cultural engagement, Māori identity, and psychological wellbeing. A methodology that incorporates both mātauranga Māori (Māori knowledge) and Western scientific knowledge bases and research methods was applied. Interviews were held with Māori students and their whānau (families) at a State secondary school where a community-driven initiative to improve Māori student outcomes took place. Thematic analysis was used to generate Te Korowai Aroha Framework, outlining how Māori cultural initiatives can enable schools to fulfil their duty of care and meet Māori community needs by affirming individuals‟ cultural identity and agency, by building relationships based on mutual respect, and by working collaboratively within the school and with external services providers. Thematic analysis of these interviews was also conducted to generate The Pōwhiri Identity Negotiation Framework. The pōwhiri (formal welcome), in which Māori creation narratives are ritually re-enacted, is used as a metaphor for Māori identity negotiation. The stages of creation Te Kore, Te Pō, Te Whaiao, and Te Ao Marama are used to describe, respectively: those who were yet to display interest in Māori cultural identities; those who were interested in developing their Māori identities; those who were actively exploring their Māori identities; and those who felt secure in their Māori identities. Quantitative longitudinal survey data from over 300 Māori adolescents in the Youth Connectedness Project was then analysed. Structural Equation Modelling revealed that Māori cultural engagement positively predicted Māori ethnic identity, and that Māori ethnic identity positively predicted psychological wellbeing, in support of hypotheses. In addition, Hierarchical Linear Modelling revealed that the higher a school‟s level of Māori cultural promotion, the higher the ethnic identity of its students was likely to be. The results of this thesis demonstrate the impact of school cultural environments on individual identity development, and provide evidence that cultural engagement initiatives can enhance Māori identities, which in turn can increase psychological wellbeing. The results from the studies presented in this thesis are incorporated into Te Pītau o te Tuakiri framework, outlining how Māori identities can be nurtured, and the results are also used to offer guidelines for individuals wishing to become more engaged in Māori culture, and institutions wishing to become more responsive to Māori communities. These findings are used to challenge educators and policy makers to ensure schools and other State institutions support Māori cultural expression and affirm Māori identities.
Keywords: colonisation; education; identity; policy; wellbeing

Rangatiratanga and Ōritetanga: responses to the Treaty of Waitangi in a New Zealand study - Wyeth, Emma H.; Derrett, Sarah; Hokowhitu, Brendan; Hall, Craig; Langley, John (Ethnicity & Health, 2010)
Introduction. Although opportunities exist for positive experiences in research, Māori in New Zealand, like other indigenous people colonised by Europeans in the nineteenth century, have also been subject to research and associated policies that have had long-lasting negative consequences. Researchers have subsequently been challenged by Māori to conduct research that is acceptable, accountable and relevant. Much of this debate has taken place within the framework of the Treaty of Waitangi, a treaty of cession signed between Māori and British Crown representatives in 1840. Nowadays, health and health research statutes exist that require researchers to respond to the ‘principles’ of the Treaty. Few practical examples of how health researchers have undertaken this have been published. Aims. We examine how, in developing a national study of injury outcomes, we responded to the Treaty. Our study, the Prospective Outcomes of Injury Study, aims to quantitatively identify predictors of disability following injury and to qualitatively explore experiences and perceptions of injury outcomes. Discussion. Responses to the Treaty included: consultation with Māori groups, translation of the questionnaire into te reo Māori, appointment of interviewers fluent in te reo Māori, sufficient numbers of Māori participants to allow Māori-specific analyses and the inclusion of a Māori-specific qualitative component. While this article is located within the New Zealand context, we believe it will resonate with, and be of relevance to, health researchers in other former settler societies. We do not contend this project represents an ‘ideal’ model for undertaking population-based research. Instead, we hope that by describing our efforts at responding to the Treaty, we can prompt wider debate of the complex realities of the research environment, one which is scientifically, ethically and culturally located.
Keywords: bicultural; policy; power; rangatiratanga; research policy; tiriti o waitangi/treaty of waitangi

How should we teach about Te Tiriti o Waitangi? Issues for raraunga (citizenship) education - Bargh, Maria; Macfarlane, Angus (Our Civic Future, 2018)
Keywords: colonisation; policy; tiriti o waitangi/treaty of waitangi

Where to for collaboration in land and water policy development in Aotearoa New Zealand? Guidance for authorising agencies - Kirk, Nicholas; Robson-Williams, Melissa; Bammer, Gabriele; Foote, Jeff; Butcher, Lian; Deans, Neil; Harmsworth, Garth; Hepi, Maria; Lilburne, Linda; Nicholas, Barbara; Small, Bruce; Turner, James A.; et al. (Kōtuitui: New Zealand Journal of Social Sciences Online, 2022)
For the past decade, collaboration has been the preferred method of devising land and water policy in Aotearoa New Zealand to achieve agreed outcomes. However, the use of collaboration in policymaking is at a crossroads, as some argue it is unrealistic to expect stakeholders and tangata whenua with competing interests to work in partnership on contentious policy issues. To help clarify the future direction of collaboration, this paper provides authorising agencies (those with responsibility for the policy problems) with prompts to reflect ex ante on the advantages and disadvantages of pursuing collaboration. Based on a retrospective review of collaborations in New Zealand’s land and water policymaking, and a two-day symposium with collaboration practitioners, we identify situations that are potentially less suited to collaboration owing to factors that are challenging to overcome through process design. Four issues that affect the success of collaborations are identified: the nature of the policy problem, the personal and collective qualities of those involved, power relationships, and the collaborative process. Finally, we draw together practical lessons from history, the symposium, and the literature to develop a list of questions for authorising agencies to use to reflect on the advantages and disadvantages of pursuing collaboration.
Keywords: co-governance; land policy; policy; water management

Whakatipu rawa ma ngā uri whakatipu: optimising the “Māori” in Māori economic development - Awatere, Shaun; Mika, Jason; Hudson, Maui; Pauling, Craig; Lambert, Simon; Reid, John (AlterNative: An International Journal of Indigenous Peoples, 2017)
One of the great challenges for indigenous and non-indigenous entrepreneurs in the twenty-first century is to move beyond profit maximisation as an acceptable modality for doing business and gravitate towards the concept of socially optimal outcomes, where maximising community well-being and minimising externalities to the natural environment and social justice are paramount. We present findings from a case-study analysis of M?ori enterprises that demonstrate a wealth of successfully kaupapa M?ori (M?ori ideology)-attuned strategy and policy. The case studies provide practical examples of the incorporation and expression of kaupapa M?ori values into strategy and policy of M?ori enterprises. We also identify the numerous challenges to implementing kaupapa M?ori in the management of M?ori Asset Holding Institutions and offer a way forward. Although the case studies are context specific, they provide some key principles and learning that can guide the greater uptake of kaupapa M?ori entrepreneurship.
Keywords: kaupapa māori; mahi; māori enterprise; māori entrepreneurship; policy

The politics and practice of counting: Ethnicity in official statistics in Aotearoa/New Zealand - Cormack, Donna (Te Rōpū Rangahau Hauora a Eru Pōmare, 2010)
The politics and practice of counting: ethnicity in official statistics in Aotearoa/New Zealand was produced as part of a broader project funded by Te Kete Hauora, Ministry of Health to investigate issues with ethnicity data in New Zealand and the implications of these for the Māori health and disability sector. The paper is one in a series of topic-based discussion papers. It aims to summarise key literature on the measurement of the Māori population in official ethnic statistics over time as a background to the accompanying discussion papers.
Keywords: crown policy; ethnic identity; ethnicity; health; health outcomes; identity; policy; statistics

Recognition and indigenizing official statistics: Reflections from Aotearoa New Zealand and Australia - Kukutai, Tahu; Walter, Maggie (Statistical Journal of the IAOS, 2015)
In First World colonised nations such as Aotearoa New Zealand and Australia, population statistics form the evidentiary base for how Indigenous peoples are known and `managed' through state policy approaches. Yet, population statistics are not a neut
Keywords: colonisation; crown policy; data sovereignty; identity; policy; self-determination; statistics

Chapter 2: "Publishing the Space": Data sovereignty and self-determination in Aotearoa New Zealand - Kukutai, Tahu; Cormack, Donna (Indigenous Data Sovereignty and Policy, 2020)
This book examines how Indigenous Peoples around the world are demanding greater data sovereignty, and challenging the ways in which governments have historically used Indigenous data to develop policies and programs. In the digital age, governments are increasingly dependent on data and data analytics to inform their policies and decision-making. However, Indigenous Peoples have often been the unwilling targets of policy interventions and have had little say over the collection, use and application of data about them, their lands and cultures. At the heart of Indigenous Peoples’ demands for change are the enduring aspirations of self-determination over their institutions, resources, knowledge and information systems. With contributors from Australia, Aotearoa New Zealand, North and South America and Europe, this book offers a rich account of the potential for Indigenous data sovereignty to support human flourishing and to protect against the ever-growing threats of data-related risks and harms.
Keywords: colonisation; data sovereignty; policy; self-determination

The Problem of Defining an Ethnic Group for Public Policy: Who is Māori and Why Does it Matter? - Kukutai, Tahu (Social Policy Journal of New Zealand, 2004)
Governments in multicultural democracies are increasingly being challenged to justify the collection of ethnic and racial data, and the targeted policies they support. Given mounting opposition to ethnicbased policies in New Zealand, it is timely to consider two questions that have arisen from ongoing debate. The first is what criteria ought to apply to determine who is Mäori for policy purposes. The second is which Mäori ought to benefit from targeted policies and programmes. This paper addresses both questions empirically and makes two suggestions: (1) that statistical and legal definitions of Mäori be amended to take account of both self-identified ethnicity and descent; (2) that programmes which seek to militate Mäori disadvantage be oriented towards those who strongly identify as Mäori, since they are the most likely to be in need.
Keywords: Inequity; data sovereignty; identity; policy; self-identification

Colonisation, hauora and whenua in Aotearoa - Moewaka Barnes, Helen; McCreanor, Tim (Journal of the Royal Society of New Zealand, 2019)
Colonisation has deeply harmed Maori communities, seriously and consistently undermining their vitality, aspirations and potentials, particularly since the 1860s, at inestimable cost to the entire nation. The British arrival in Aotearoa commenced a relationship between two very different peoples that has profoundly influenced their distinct and collective fortunes ever since. Despite manifest breaches of te Tiriti o Waitangi, this relationship has centred settler interests ensuring that Maori sovereignty has been displaced in favour of colonial hegemony, entrenching longstanding, preventable inequities in health and other important domains of social life. In this paper we trace some broad indicators of relational health and wellbeing in Aotearoa and consider how Maori thinking about whenua, health and wellbeing might lead healing opportunities for people and whenua. We outline ways in which a unified, dynamic, relational Maori concept based on whenua as the determinant of health could contribute. We believe this could expand, strengthen and revitalise prevention, protection and promotion approaches, to counter the injustices of colonisation, contribute toward health equity and move toward just, sustainable shared futures for the benefit of all New Zealanders.
Keywords: colonisation; disparities; hauora; health; policy; regeneration; social determinants; sovereignty; tiriti o waitangi/treaty of waitangi; whenua